Contribution to the lady beetle fauna of the Yucatan Peninsula and integrative taxonomy for species delimitation. Issue 1 (31st December 2022) - Catzim, Vannesa V.; Elías-Gutiérrez, Manuel; Pérez-Lachaud, Gabriela
Abstract : Lady beetles (Coleoptera: Coccinellidae) are among the most familiar insects; many species are of economic importance, but their diversity in the tropics is poorly known. We aimed to contribute to the knowledge of the lady beetle fauna of the Yucatan Peninsula, particularly for Quintana Roo state. We used an integrative approach for species identification, comparing classical morphological identifications and quick automated methods for species delimitation using DNA barcode sequences. Through a literature review and a survey of lady beetles in gardens in Quintana Roo, we further provide an updated list of the species found on the Yucatan Peninsula. Out of the 40 species delimited in our study, 34 are new reports for the peninsula, and 36 are new for Quintana Roo state. Overall, 62 species of lady beetles are now recorded for the entire region, including three exotics: the invasive Harmonia axyridis, Chilocorus nigrita, and Delphastus catalinae. Our study also contributed to public reference libraries with 110 barcode sequences for the tropics belonging to 34 delineated species. We showed that cytochrome oxidase 1 (COI) sequences can be useful for lady beetle species delimitation and that the Automatic Barcode Gap Discovery algorithm (ABGD) was the best method, complementing the number of initially delineated morphospecies. The Barcode Index Number (BIN) approach overestimated seven putative species due to the splitting of conspecifics, while the ABGD method suggested two additional MOTUs at a prior intraspecific distance of 0.059. Combined molecular and morphological data in our study revealed one additional putative species of Diomus, initially considered a tentative colour variation. Our study exemplifies how molecular methods paired with classical taxonomy can efficiently assist in delineating species when descriptions and identification keys are unavailable and highlights the possible great richness of coccinellid species awaiting exploration and description on the Yucatan Peninsula.